2016
DOI: 10.1063/1.4952434
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and kinetics of defects in Li2S

Abstract: Li2S is the final product of lithiation of sulfur cathodes in lithium-sulfur (Li-S) batteries. In this work, we study formation and diffusion of defects in Li2S. It is found that for a wide range of voltages (referenced to metal Li) between 0.17 V and 2.01 V, positively charged interstitial Li (Li+) is the most favorable defect type with a fixed formation energy of 1.02 eV. The formation energy of negatively charged Li vacancy (VLi−) is also constant, and it is only 0.13 eV higher than that of Li+. For a narro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 37 publications
7
23
0
Order By: Relevance
“…Understanding the transport properties of the S and Li 2 S REMs is a prerequisite for the development of rational strategies to improve the capacity, efficiency, and cycle life of Li-S batteries. Nevertheless, transport mechanisms in these compounds have not been widely studied, especially in the case of S. [38][39][40][41] While a few studies exist for Li 2 S, consensus regarding the dominant charge-carrying species has been slow to emerge. For example, Kang et al reported that the dominant charge carriers in Li 2 S are negative Li and positive S vacancies, based on calculations performed at the hybrid functional level of theory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the transport properties of the S and Li 2 S REMs is a prerequisite for the development of rational strategies to improve the capacity, efficiency, and cycle life of Li-S batteries. Nevertheless, transport mechanisms in these compounds have not been widely studied, especially in the case of S. [38][39][40][41] While a few studies exist for Li 2 S, consensus regarding the dominant charge-carrying species has been slow to emerge. For example, Kang et al reported that the dominant charge carriers in Li 2 S are negative Li and positive S vacancies, based on calculations performed at the hybrid functional level of theory.…”
Section: Introductionmentioning
confidence: 99%
“…41 Moradabadi and co-workers found that the dominant charge carriers were Li vacancies and Li interstitials, based on calculations employing a semi-local functional. 39 (Li interstitials were not considered in Refs. 27 and 41 .)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This coupling is most relevant in Li-ion batteries, where due to charging/discharging processes, bulk and interfacial as well as thermal strains can occur. The fact that induced stresses, which raise during intercalation, could weaken the interface between electrode/electrolyte and finally degrade the battery performance has been extensively discussed in the past [16][17][18][19][20][21][22][23][24][25][26][27]. Much less is known, however, about the coupling of strain fields to the formation and migration of Li vacancies in the bulk part of the material.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Theoretical simulations, in particular based on density functional theory (DFT) calculations, have been successfully applied to evaluate diffusion barriers [11,12,14] andf ormation energies. [12,13,15,16] The formation of Schottky pairs consisting of Li + and F À vacancies for av oltage range of 0-4 Vh as been con-firmed for the rock-salt LiF crystal using DFT calculations and thermodynamic considerations. [12] Shi, et.…”
Section: Introductionmentioning
confidence: 99%